Perancangan dan Realisasi Produk Petit-Pot Bersama UMKM Rattancious - Sabrina Versika Gosang; Finalia Finalia; Elizabeth Gina Mitayanny Salim (Universitas Serang Raya, 2019)
The purpose of the service program is to develop small businesses that are economically independent with creative and innovative ideas. The business partners in this program are small business MSMEs that produce local wicker-based handicrafts named Rattancious which was founded by Erick Budiman Soetanto. The problems faced by partners are the lack of product innovation with the mindset of less innovative small entrepreneurs, lack of market share and promotional activities, lack of understanding of management management and allocation of operational funds. The method of implementing service activities is in the form of assistance to optimize management management with creative and innovative ideas and entrepreneurial values. The results achieved are the creation of Petit-Pot which is a local rattan-based handicraft product made from creative ideas of collaboration with partners. Petit-pot is a mini-sized container made of rattan where the pot is made in the form of simplification of cute and cute animals. This assistance program is expected to be able to facilitate the development of partner businesses and then be able to provide a multiplier effect for similar businesses and other related businesses.